2017
DOI: 10.1016/j.bmcl.2017.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Ester- and amide-containing multiQACs: Exploring multicationic soft antimicrobial agents

Abstract: Quaternary ammonium compounds (QACs) are ubiquitous antiseptics whose chemical stability is both an aid to prolonged antibacterial activity and a liability to the environment. Soft antimicrobials, such as QACs designed to decompose in relatively short times, show the promise to kill bacteria effectively but not leave a lasting footprint. We have designed and prepared 40 soft QAC compounds based on both ester and amide linkages, in a systematic study of mono-, bis-, and tris-cationic QAC species. Antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…Additionally, the effect of the n = 3 linker length of honokiol/magnolol derivatives on the antibacterial activities against S. aureus was similar to that of the n = 3 linker length of some quaternary ammonium compounds (QAC) reported by Minbiole and co-workers. 48,49 Additionally, to further validate that the precursors honokiol and magnolol are crucial for the antibacterial activity, we replaced the honokiol/magnolol moiety with phenol and 4allylphenol, preparing compounds 7 and 8 by the same method as 5i (Scheme S1) and evaluating their antibacterial activities against S. aureus and 10 clinical MRSA isolates. The MICs of 7 and 8 were all greater than 64 μg/mL (Table S2), indicating that the honokiol/magnolol part plays an important role in the antibacterial activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, the effect of the n = 3 linker length of honokiol/magnolol derivatives on the antibacterial activities against S. aureus was similar to that of the n = 3 linker length of some quaternary ammonium compounds (QAC) reported by Minbiole and co-workers. 48,49 Additionally, to further validate that the precursors honokiol and magnolol are crucial for the antibacterial activity, we replaced the honokiol/magnolol moiety with phenol and 4allylphenol, preparing compounds 7 and 8 by the same method as 5i (Scheme S1) and evaluating their antibacterial activities against S. aureus and 10 clinical MRSA isolates. The MICs of 7 and 8 were all greater than 64 μg/mL (Table S2), indicating that the honokiol/magnolol part plays an important role in the antibacterial activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A significant contribution to the development of QACs as a class of cationic biocides was made by the groups of Wuest and Minbiole (Figure 17) [71][72][73][74][75][76]. It was found that close structural analogs of BAC 37 containing amide and ester groups exhibited comparable activity and lower toxicity than BAC [76].…”
Section: Single-charged Qacs (Mono-qacs)mentioning
confidence: 99%
“…A significant contribution to the development of QACs as a class of cationic biocides was made by the groups of Wuest and Minbiole (Figure 17) [71][72][73][74][75][76]. It was found that close structural analogs of BAC 37 containing amide and ester groups exhibited comparable activity and lower toxicity than BAC [76]. QAC derivatives of natural compounds (quinine 38 and nicotine 39) demonstrated a wide spectrum of antibacterial action, thus justifying the search for other platforms of natural origin to expand the library of active QAC compounds [74].…”
Section: Single-charged Qacs (Mono-qacs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several soft cationic QACs showed biological activities against several pathogenic bacterial strains [16], filamentous fungi [17] and also some human tumor cell lines [18]. Therefore, soft cationic QACs can potentially be used in lysosometargeting anti-cancer drugs [19][20][21]. Cationic QACs can enter the lysosome and possibly induce conformational changes of the proteins involved in apoptosis [22].…”
Section: Introductionmentioning
confidence: 99%